ISLAMIC HISTORY THROUGH A WESTERN LENS: A CRITICAL ANALYSIS OF KEY INTRODUCTORY WORKS (2010-2025) - DR. TAUSEEF AHMAD PARRAY (Hamdard Islamicus)
Western academia has witnessed a rapid proliferation of literature on Islam, particularly in the post-9/11 era. A notable portion of this corpus consists of ‘introductory works’, predominantly authored by ‘American Islamicists’. This study critically analyzes how Islam is portrayed in a limited selection of significant introductory textbooks published (in revised editions) between 2010 and 2025. Using critical content analysis, the findings reveal a conflict between a sophisticated understanding of Islamic intellectual traditions and the framing of Islam within Western epistemological contexts. This study aims to enhance readers’ understanding of current pedagogical and epistemological trends in Western studies of Islam, highlighting the importance of critical self-reflection, diverse perspectives, and culturally attuned teaching methods.